Lymphocyte count and partial pressure of oxygen can be used as a screening test for COVID-19 in secondary care (2020)
In United Kingdom (UK) secondary care, identification of SARS-CoV-2 – aetiological agent for Coronavirus Disease 2019 (COVID-19) – is reliant on polymerase chain reaction (PCR) testing of nasopharyngeal swabs. Whilst PCR testing capabilities and turnaround times have improved nationally, results are rarely available when critical cohorting and treatment decisions are made thus delaying appropriate management and exposing susceptible patients and staff to patients with COVID-19. A quick, clinically applicable screening test in secondary care is needed on admission to help in the appropriate isolation and cohorting of patients, especially with the increasing prevalence of COVID-19 and the impending seasonal increase in other respiratory tract infections. As respiratory symptoms and lymphopaenia secondary to COVID-19 have been well described previously1–3, we performed a study of consecutive patients to determine whether lymphocyte count and partial pressure of oxygen (pO2) on admission can be used as a screening test for COVID-19 in UK secondary care.